THE ROLE OF WEAVERS WOMAN IN STRENGTHENING NATIONALISM Case Study in Sajingan Besar Frontier, Indonesia - Elyta Elyta; A Razak (Universitas Padjadjaran, 2019)
Woven crafts made by women at the Sajingan Besar frontier, besides that it also has economic value, historical value, cultural values that show the identity of the population at the national boundary. The aims of the study were to describe the role of weavers’ women in strengthening nationalism, woven is a culture that is typical of the society in Sajingan Besar frontier, Sambas District. There are two data used in this paper, i.e primary data is field studies, and secondary data is literature studies. The result of research shown that there is an important role from weavers’ women in Sajingan Besar, namely: (1) Utilization of Natural Resources is to strengthen nationalism by utilizing the availability of natural resources in managing them into woven crafts which are a form of expansion of nationalism because woven crafts are a cultural heritage and has local characteristics of Sajingan Besar, (2) The Role of weavers’ women in Sajingan Besar is able to realize a harmonious life with the Malaysian community to strengthen nationalism has become a role model on the frontier whose territory is inhabited by a variety of different tribes, religions and cultures but unity is maintained.